Localization of Fibrinolytic Activity in Myocardial Infarcts in Rats - Kwaan, H. C; Astrup, T (Thrombosis and Haemostasis, 1964)
Acute myocardial infarction was produced in rats by ligation of the left coronary artery. Different phases of healing, up to 6 weeks, were studied in order to compare its normal histology with the appearance and localization of fibrinolytic activity.The fibrinolytic activity was studied by the histochemical method using plasminogen rich fibrin substrate for demonstration of plasminogen activator, and a plasminogen free fibrin substrate (heat treated) for protease estimation. In all the specimens studied only plasminogen activator was detected.The usual morphological features were essentially the same as those described by previous authors. The fibrinolytic activity in the normal ventricular wall was sparsely distributed and was localized to the small blood vessels. In the early infarct fibrinolytic activity had disappeared, but it reappeared in the thrombosed small blood vessels as organization and recanalization took place. It was present in increased amounts in the newly formed blood vessels growing into the infarcted area and persisted in these vessels after healing was complete though slowly decreasing in frequency of distribution and in concentration. The results show that healing of myocardial infarcts follows the pattern of a normal tissue repair process, and they substantiate the role of the fibrinolytic system in wound healing.